Lorsque l’entrée dans le monde scolaire se heurte aux modèles d’enfant et de parent attendus - Xavier Conus (Recherches en Éducation)
The recognition of the positive value of student diversity and their right to full participation are key aspects of inclusion as a means of managing heterogeneity of the school population in an equality perspective. As the school cannot welcome the diversity of children without including their families, the same logic needs to apply to the relationship between the school and parents, particularly in the current environment where the school-family partnership appears as a privileged institutional leverage in the fight against inequalities at school. Based on an ethnographical study exploring how the relationship between the school and the families builds up in a Swiss school located in a context of strong cultural diversity, this paper interrogates how the school norm can be the main limitation to the inclusion of students and parents who are unfamiliar with school. Derived from field observations and interviews, our results show how the teachers can consider their relation with new students and parents from the standpoint of narrow expected models, leading them to engage in a vain attempt to conform the students and parents when they differ from these standards. The possibility of entering the school system for students and parents unfamiliar with school is hindered by the exclusive and excluding normativity on which the models of the child and the parent expected by the teachers are grounded. Based on these observations, we discuss how we feel that inclusion requires in the first place a necessary process of decentring from the school and teachers, as a condition for recognition of the actual child and parent.